Deck codes + standards : how to design, build, inspect + maintain a safer deck - Barker, Bruce A. (Cool Springs Press, 2025)
A certified residential combination inspector and building code expert provides essential guidance for designing and building safe decks with photos and illustrations, addressing common issues with updated codes and ensuring your deck meets inspection standards while preventing potential disasters.